2017
DOI: 10.1097/fch.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Models of Care Delivery for Patients With Parkinson Disease Living in Rural Areas

Abstract: The elderly who suffer from chronic conditions have an increasingly difficult time accessing health care in rural areas compared with their healthy counterparts who seek and utilize less specialty care. Parkinson disease affects approximately 0.3% to 5% of the elderly population. However, a large portion of that population has difficulty accessing health care. The purpose of this study was to obtain an understanding of the access to care issues for patients with Parkinson disease and review solutions to aid th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Poor interprofessional coordination between healthcare settings exists in the care of Parkinson's disease [6,28]. A significant gap in care is experienced when people with Parkinson's disease try to access various interprofessional specialists for the confirmation of their diagnosis, services for mental health problems and physiotherapy, despite the fact that existing international guidelines recommend quick referral processes and prompt access to specialist care to uphold the best outcome for patients [7,12,13,15].…”
Section: Inappropriate Delivery Of Healthcare Servicesmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor interprofessional coordination between healthcare settings exists in the care of Parkinson's disease [6,28]. A significant gap in care is experienced when people with Parkinson's disease try to access various interprofessional specialists for the confirmation of their diagnosis, services for mental health problems and physiotherapy, despite the fact that existing international guidelines recommend quick referral processes and prompt access to specialist care to uphold the best outcome for patients [7,12,13,15].…”
Section: Inappropriate Delivery Of Healthcare Servicesmentioning
confidence: 99%
“…The literature highlights that access to healthcare services for people with Parkinson's disease is not always easy. Studies have reported that delays in diagnosis, a lack of appropriate healthcare services, especially in underservices regions, extensive waiting lists for specialist services, and the cost of care are some of the barriers to access healthcare services [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research-grade eye tracking using expensive instrumentation in the laboratory provides a means of identifying various neurological disorders 15 , 16 including accurately and precisely quantifying individual oculomotor abnormalities in ataxias 17 . However, this is only available in specialized centers and are even less accessible in rural areas and to disease populations where mobility is affected 18 . Furthermore, frequent and longitudinal assessments for tracking disease severity in a clinical trial and interval monitoring of presymptomatic gene carriers to identify clinical onset may be less practical using these technologies.…”
Section: Introductionmentioning
confidence: 99%
“…These factors are argued to impede the management of PD in regional areas, including for sleep disorder (Duncan and Rositano, 2011). "Regional living" is a risk factor for PD; a high proportion of patients with PD live in regional areas (Schuller et al, 2017;Soh et al, 2012).…”
Section: Introductionmentioning
confidence: 99%